Using graph-analytical methods modeling of system objects to determine integrated assessment of their state - Kozulia, T.V.; Kozulia, M.M. (Вопросы атомной науки и техники, 2019)
In article is determined of object state in researching "system - environment" based on system analytic-graph modeling for representation real relationships and relations between any systems in nature. Justified non-standard solution according to forecasting states and changes results in "system - environment" based on constructed cognitive models and entropy analysis for action direction sustainability and implemented situations assessment. Practical usage of systematic methodological support for complex objects comprehensive research based on graph models sequential analysis. To analyze physical processes displacements between simple ideal system components, which are sources of potential and kinetic energy, changes in its capacity through matter or energy accumulation, is used structural graph-physical processes topological model. Визначено стан об'єкта при дослідженні "система - середовище", заснованого на системном граф-аналітичному моделюванні для представлення реальних зв'язків та відносин між будь-якими системами в природі. Обгрунтоване нестандартне рішення за прогнозними станами та змінами призводить до стану "системи - середовища", що базується на побудованих когнітивних моделях та аналізі ентропії для оцінки стійкості напрямку діяльності та реалізації ситуації. Практичне використання систематичної методологічної підтримки комплексних об'єктів комплексного дослідження базується на послідовному аналізі моделей графів. Для аналізу фізичних процесів зміщення між простими компонентами ідеальної системи, які є джерелами потенційної та кінетичної енергії, зміни його потужності через накопичення речовини або енергії, використовується структурний граф-топологічна модель фізичних процесів. Определено состояние объекта при исследовании "система - среда", основанного на системном граф-аналитическом моделировании для представления реальных связей и отношений между любыми системами в природе. Обоснованное нестандартное решение по прогнозным состояниям и изменениям приводит к состоянию "система - среда", основанному на построенных когнитивных моделях и анализе энтропии для оценки устойчивости направления деятельности и реализации ситуации. Практическое использование систематической методологической поддержки комплексных объектов комплексного исследования базируется на последовательном анализе моделей графов. Для анализа физических процессов смещения между простыми компонентами идеальной системы, которые являются источниками потенциальной и кинетической энергии, изменения его мощности через накопление вещества или энергии, используется структурная граф-топологичная модель физических процессов.